2022
DOI: 10.1029/2021gl096213
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Electrons by Whistler‐Mode Hiss Waves at Saturn

Abstract: The importance of whistler-mode chorus in locally accelerating electrons is well known at the Earth (Horne et al., 2005;Reeves et al., 2013) and has recently been found to be important at Jupiter and Saturn (Horne et al., 2008;Woodfield et al., 2014Woodfield et al., , 2019. Whilst chorus is a plasma wave observed in discrete rising or falling tones observed in two frequency bands separated by half the electron gyrofrequency (Li et al., 2011), whistler-mode hiss is a broadband emission at the lower end of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Plasmaspheric hiss has been observed at the magnetized planets. At Saturn, studies show that there are regions where the plasma density is sufficiently small that hiss can actually accelerate electrons and contribute to the Saturnian radiation belt [287].…”
Section: Plasmaspheric Hissmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmaspheric hiss has been observed at the magnetized planets. At Saturn, studies show that there are regions where the plasma density is sufficiently small that hiss can actually accelerate electrons and contribute to the Saturnian radiation belt [287].…”
Section: Plasmaspheric Hissmentioning
confidence: 99%
“…At Jupiter, the chorus has been suggested as providing the missing acceleration needed to produce 50-MeV electrons that emit synchrotron radiation from the planet [332]. At Saturn, similar wave acceleration processes involving chorus [333], Z mode waves [334], and hiss [287] are now suggested to play a key role in the origin of the Saturnian radiation belt.…”
Section: Chorus Wavesmentioning
confidence: 99%
“…Besides ECH waves, other wave modes including whistler‐mode chorus waves (Menietti et al., 2013), hiss waves (Menietti et al., 2019; Woodfield et al., 2022), Z‐mode waves (Menietti et al., 2016; Wu et al., 2021; Ye et al., 2009, 2010), and ion cyclotron waves (e.g., Leisner et al., 2005, 2006, 2011; Long et al., 2022; Russell et al., 2006) are also frequently observed in Saturn's magnetosphere. These plasma waves are recognized to significantly impact the local acceleration and loss processes of Saturn's radiation belt electrons by wave‐particle interactions (e.g., Cao et al., 2023; Gu et al., 2013; Kollmann et al., 2018; Menietti et al., 2012; Woodfield et al., 2018, 2019, 2022; Yu et al., 2019). It is also reported that ECH waves could interact with electrons in the energy range from ∼10 eV to several keV, leading to the generation of diffuse aurora (Tripathi et al., 2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…A large variety of physical processes have been proposed to be responsible for the dynamic evolution of radiation belt electrons at Saturn (Kollmann et al., 2017; Roussos & Kollmann, 2021; Shprits et al., 2012), among which, resonant interactions with plasma waves play an important role (Yao et al., 2021). Various plasma wave modes, for example, whistler‐mode chorus waves (Menietti et al., 2013, 2014; Woodfield et al., 2019; Yu et al., 2019a), auroral hiss (Woodfield et al., 2022) and Z‐mode waves (Gu et al., 2013; Menietti et al., 2016; Woodfield et al., 2018; Ye et al., 2010), contribute significantly to the local acceleration and loss of Saturn's radiation belt electrons. Ion cyclotron waves, which are frequently observed inside the region of Saturn's radiation belt with strong averaged amplitudes, are likewise expected to resonate effectively with radiation belt electrons.…”
Section: Introductionmentioning
confidence: 99%